STRATEGIC MANAGEMENT PRACTICES AND TEACHER ENGAGEMENT: AN IMPACT ANALYSIS ON SCHOOLS - Rosita, Tita; Rahayu, Ucu; Sagita, Dony Darma (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to analyze the relationship between strategic management, teacher participation, and school performance in public elementary schools, focusing on how leadership practices influence institutional outcomes. The research addresses a growing need to understand how strategic decision-making processes can be effectively aligned with grassroots teacher involvement to enhance educational quality and accountability. This study employs a quantitative correlational design using a validated and reliable 5-point Likert scale questionnaire administered to randomly selected public elementary school teachers. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the hypothesized relationships among the three key variables. The results show that strategic management has a strong positive influence on teacher participation, with a contribution of 81.1%, and significantly impacts school performance with a contribution of 68.5%. However, the rejection of the third and fourth hypotheses which posited that teacher participation would mediate the relationship between strategic management and school performance suggests that teacher involvement in strategic planning is still peripheral rather than integral. External factors such as educational policy limitations, resource disparities, and administrative rigidity are identified as contributing barriers. This study introduces a novel model that maps the strategic alignment between management practices and teacher engagement, offering a deeper understanding of why participatory leadership may fail to translate into improved outcomes. It recommends a collaborative strategic management framework that genuinely embeds teacher input to optimize school performance and create sustainable educational change.